Constraining the Gamma-Ray Burst Jet Opening Angle Based on the Very Steep Decay Phase - Qian Xu; Dong-Jie Liu; Yuan-Chuan Zou (The Astrophysical Journal)
Thanks to the rapid follow-up observations by the Swift X-Ray Telescope (XRT), a good part of gamma-ray bursts' (GRBs) high-latitude emission have been observed in the X-ray band. Some even show a dropdown decay after this period, which strongly indicates the edge of the jet is corresponding to the breaking time. This study constrains the jet opening angles of GRBs by analyzing the very steep decay phase in the early X-ray afterglow. Using data from Swift/XRT, we identified GRBs with significant breaks in their light curves and applied a broken power-law model to describe the decay phases. Assuming a spherical and isotropic emitting surface, we set constraints on the radiation radius ( R _γ ) to estimate jet opening angles ( θ _jet ) from the breaking time. Our results indicate that jet opening angles can be constrained, although they are sensitive to the assumed radiation radius. This approach provides yet another method for estimating GRB jet opening angles.